Synthesis of an oxygen-permeable block copolymer with catechol groups and its application in polymer-ceramic pressure-sensitive paint. (16th March 2020) - Obata, Makoto; Yamai, Kouta; Takahashi, Masaki; Ueno, Shintaro; Ogura, Hiroya; Egami, Yasuhiro
Abstract: An oxygen-permeable block copolymer, poly (2, 2, 2-trifluoroethyl- co -isobutyl methacrylate)- b -poly ( N -acryloyldopamine) (FEM- b -PDOPA), in which the PDOPA segment acts as an adhesive section to attach TiO2 nanoparticles, was successfully synthesized via RAFT polymerization followed by a post-polymerization modification with dopamine. Conjugates of FEM- b -PDOPA with TiO2 nanoparticles were prepared by mixing them in chloroform and methanol. IR and solid-state CP-MAS 13 C NMR spectroscopies clearly indicated the presence of FEM on the TiO2 nanoparticles. Thermogravimetric analysis of the resulting nanoparticles indicated that FEM- b -PDOPA, rather than FEM alone, was tightly bound to the TiO2 nanoparticles, and that the weight fraction was 2.5 wt%. Polymer-ceramic pressure-sensitive paint was prepared by mixing a luminescent dye, FEM, and TiO2 treated with either FEM- b -PDOPA or native TiO2 . In comparison with the coating prepared using native TiO2, the pretreatment of TiO2 with FEM- b -PDOPA effectively reduced the photodegradation of the luminescent dye without deterioration in pressure and temperature sensitivity or dynamic response performance. Graphical abstract: Image 106 Highlights: An oxygen-permeable block copolymer, FEM- b -PDOPA, was successfully prepared. The binding ability of a PDOPA segment to TiO2 particles was characterized by TGA. A pre-treatment of TiO2 with FEM- b -PDOPA improved the photostability of the coating.